Program Ayu Ting-Ting (Atasi Yuk stunTing, Itu penTing) Bersama Kita Entaskan Stunting Melalui DASHAT (Dapur Sehat Atasi Stunting) - Muhammad Anshari; Herda Ariyani; Dewi Nurhanifah; Ach Lutfi Arianto; Aina Habibah; Amalia Safitri; Anisa Fitri Syahrida; Fatimatul Zahra; Maulinda Nur Pramudyas; Muhammad Naufal Rismana; Vivi Mardiani; Wanda Syahrina; Annisa Dwi Oktaviana (Borneo Community Development, 2024)
Stunting is an urgent issue to be addressed seriously and collaboratively. The purpose of this activity is to understand to the community of Village Bi-ih about the importance of preventing stunting, improvement of the consumption of public food from various available, nutritious and affordable foods through training Healthy Food Menu as well as the development of Healthy Lifestyle. The method of implementation of community service is carried out with the method of participatory approach where the entire activity involves partners and society. The DASHAT (Healthy Kitchen on Stunting) accompanying activities were held in the Village Office Hall of Bi-ih and attended by a total of about 30 people consisting of 20 families at stunting risk and 10 village CTC cadres. While activities for the youth element can create an interactive and exciting learning experience with the media game snake ladder Ayu Ting Ting (Atasi Yuk stuntTING, it's pen) as a stunting literature on high school students Muhammadiyah Village Bi-ih. The activity was successful in training the skills of caders and families at stunting risk in the creation of healthy food menus, knowledge of how to process food hygienically and correctly for the age of the child, as well as training Clean and Healthy Lifestyle.